Isomorphism and 'capability trap' in the South African Public Service - Thani, X. C. (IPADA, 2019)
As stipulated in sections 26, 27 and 29 of the Constitution of the Republic of South Africa of 1996, public institutions are mandated to legislative measures in delivering services to the public. This mandate has to be fulfilled by public institutions regardless of the enormous pressure by internal and external pressure. This pressure compels South African public service to willingly/unwillingly transform and adopt appropriate models for improved service delivery. When enhancing service delivery, government departments often than not unconsciously experience isomorphism, which is later explained in this paper. In some instances, isomorphism leads to 'capability trap', which results to an institutional failure exacerbated by the state of isomorphic mimicry. The purpose of this paper is to answer the question, to what extent is the South African public service experiencing isomorphism? Subsequently, it is important to ask whether isomorphism leads to capability trap that various public institutions are seen to be experiencing recently. These questions are explored by undertaking a critical literature review adopting a hermeneutic reading modality, which is grounded in qualitative studies. It is the intention of this paper to derive the meaning and understanding of the isomorphic state of the South African public service. This paper firstly conceptualises isomorphism and further identify and conceptualise the various forms of isomorphism. State capability trap is deliberated upon in order to demonstrate the extent of isomorphism in the South African public service. This section is followed by examples that indicate the influence of isomorphism in public administration. Concluding remarks summarise this paper and propose mechanisms that could be put in place to avoid isomorphism. Keywords: Isomorphism, Isomorphic mimicry, Capability trap, Public service, Hermeneutic
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Isomorphism; Isomorphic mimicry; Capability trap; Public service; Hermeneutic; Isomorphism (Crystallography)